In the name of liberalism Illiberal social policy in the United States and Britain - King, Desmond (New York Oxford University Press, 1999)
Annotation Why have British and North American governments adopted illiberal social policies during this century? In the Name of Liberalism investigates examples of social policy in Britain and the United States that conflict with liberal democratic ideals. The book examines the use of eugenic argumentsin the 1920s and 1930s, the use of work camps in the 1930s as a response to mass unemployment and the introduction of work-for-welfare programs since the 1980s. The book argues that existing accounts of American and British political development neglect how illiberal social policies are intertwined in the creation of modern liberal democratic institutions. Such policies are, paradoxically, justified in terms of the liberal democratic framework itself. Inthe light of the books research, the author suggests that there is a need to know more about the internal workings of democracies to justify the claim that liberal democracy represents the most attractive set of political institutions.